Pictographic Representations of the Word “Nature” in Preschool Education Children - Fraijo-Sing, Blanca Silvia; Beltrán Sierra, Norma Isabel; Tapia-Fonllem, César; Valenzuela Peñúñuri, Rosalba (Frontiers in Psychology, 2020)
The relevance of preschool children's understanding of nature, its elements, how it affects the behavior of human beings and how human being influences it, it helps to the identification of the necessary elements for the design of programs that have a significant impact in the development of environmental identity and the implementation of environmental education in the school curriculum in Mexico, in order to achieve the derivation of attitudes to preserve the environment from an early age. Under this logic, the objective of the present study was to identify the components of the concept Nature, from drawings made by preschool children in a desert environment, this through a visual discursive analysis. It was made by 118 preschool students, whose ages range between 5 and 6 years; enrolled in four different schools in Hermosillo, Mexico, three located in the urban area and one on the coast of the State of Sonora. Participants were asked to draw the first thought that came to their minds when they heard the word nature. As a result, it was obtained with the representations of the images, that all the drawings present categories such as plants, animals, water bodies, celestial bodies, abiotic factors, natural locations, locations made by man and others. Finally, it was discovered that the analyzes showed a generalized idea of what nature represents by including elements of known flora and fauna, however, they did not capture elements of the desert region in which they live.